2016
DOI: 10.1017/s136898001600118x
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Healthy Eating Index-2010 to the hunger relief system

Abstract: Calculating HEI-2010 for food shelves using electronic invoice data is novel and feasible, albeit with limitations. HEI-2010 scores for 2013 identify room for improvement in nearly all food shelves, especially the smallest agencies. The utility of providing HEI-2010 scores to decision makers in the hunger relief setting is an issue requiring urgent study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 26 publications
2
36
1
Order By: Relevance
“…25 But another study showed lack of cultural accommodation and language barriers for Spanish-speaking clients, serving as impediments to equitable food provision. 32 Research on availability demonstrates that the selection of food offerings from pantries is generally inadequate to support healthful diets, 21,27,[57][58][59] with mixed results in terms of dietary outcomes. 24,25 Regarding acceptability, one study focusing on the perspective of pantry clients identified factors not identified in the current study; i.e., stigma and shame were barriers to access, and dignity was a facilitator.…”
Section: Discussionmentioning
confidence: 99%
“…25 But another study showed lack of cultural accommodation and language barriers for Spanish-speaking clients, serving as impediments to equitable food provision. 32 Research on availability demonstrates that the selection of food offerings from pantries is generally inadequate to support healthful diets, 21,27,[57][58][59] with mixed results in terms of dietary outcomes. 24,25 Regarding acceptability, one study focusing on the perspective of pantry clients identified factors not identified in the current study; i.e., stigma and shame were barriers to access, and dignity was a facilitator.…”
Section: Discussionmentioning
confidence: 99%
“…When measured in recent years, pantries have demonstrated room for improvement, 8 and face particular challenges in offering adequate fruit, dairy, and whole grains. 8 Assessments with hunger relief agencies indicate their desire to monitor their food quality through automated processes, 9 but adopting new practices is challenging. Pantries have a limited capacity to track food from multiple sources (food bank orders, retail rescue, donations) as it moves through the pantry.…”
Section: Introductionmentioning
confidence: 99%
“…One such tool, the U.S. Department of Agriculture’s (UDSA) Healthy Eating Index-2010 (HEI-2010) was tested as a means for pantries to monitor the nutritional quality of their food. 8 The HEI-2010 is an updated version from HEI-2005 and assesses how well a set of foods aligns with the Dietary Guidelines for Americans. 1517 Scores are calculated by summing 12 nutrient subcomponents for a total score of 0–100 according to USDA standards, with higher scores indicating better alignment with recommendations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutritionally dense foods and beverages include "vitamins, minerals, and other substances that contribute to adequate nutrient intakes or may have positive health effects, with little or no solid fats and added sugars, refined starches, and sodium" (USDHHS & U.S. Department of Agriculture [USDA], Office of Disease Prevention and Health Promotion, 2015). Validated approaches to quantify the nutritional density of foods have been defined in the literature (Fulgoni, Keast, & Drewnoswski, 2009;Nanney et al, 2016). The Nutrient-Rich Food Index (NRFI; Fulgoni et al, 2009) is based on the nutritional composition per calorie of nine nutrients to encourage and three nutrients to limit (Figure 1).…”
Section: Introductionmentioning
confidence: 99%